Coupling of an individual-based population dynamic model of Calanus finmarchicus to a circulation model for the Georges Bank region - MILLER, CHARLES B.; LYNCH, DANIEL R.; CARLOTTI, FRANÇOIS; GENTLEMAN, WENDY; LEWIS, CRAIG V. W. (Fisheries oceanography, 1998)
An individual‐based life history and population dynamic model for the winter–spring dominant copepod of the subarctic North Atlantic, Calanus finmarchicus, is coupled with a regional model of advection for the Gulf of Maine and Georges Bank. Large numbers of vectors, each representing individual copepods with elements for age, stage, ovarian status and other population dynamic variables, are carried in a computation through hourly time steps. Each vector is updated at each time step according to development rate and reproductive functions derived from experimental data. Newly spawned eggs are each assigned new vectors as needed. All vectors are subject to random mortality. Thus, both life history progression and population dynamics of C. finmarchicus are represented for the temperatures in the Gulf of Maine–Georges Bank region in the active season. All vectors include elements representing depth, latitude and longitude. This allows coupling of the population dynamics to the tide‐ and wind‐driven Dartmouth model of New England regional circulation. Summary data from the physical model are used to advance vectors from resting‐stock locations in Gulf of Maine basins through two generations to sites of readiness for return to rest. Supply of Calanus stock to Georges Bank comes from all of the gulf and from the Scotian Shelf. The top of the bank is stocked from western gulf basins; the North‐east Peak is stocked from Georges Basin and the Scotian Shelf. All sources contribute to stock that accumulates in the SCOPEX gyre off the north‐west shoulder of Georges Bank, explaining the high abundance recurrently seen in that region. There is some return of resting stock to Wilkinson Basin in the western gulf, but other basins must mostly be restocked from upstream sources to the north‐east.